Social Work with Children from Severe Materially and Psychologically Deprived Families. A study for Displaced Families in Erbil camps - Salih, Asst.L.Hazha Mohammed Salih; Azeez, Asst.L.Muzhda Mohammed Azeez; Taha, Dr. Hakim Qadir Taha (Sulaimani Journal for Humanities, 2026)
This study investigates the effectiveness of social work interventions in meeting the needs of children from severely deprived families residing in displacement camps, particularly focusing on the Dara Shakran camp for Syrian refugees in Erbil, Kurdistan Region. Through qualitative research methods, including semi-structured interviews with a diverse range of participants, the study aims to identify the primary material and psychological needs of children in the camp, assess existing social work interventions, explore barriers to accessing services, and examine the influence of cultural factors on intervention effectiveness. Findings highlight significant challenges faced by children and families in the camp, including difficult living conditions, poverty, limited educational opportunities, psychological distress, and inadequate support from social workers and NGOs. The study underscores the complexity of addressing the needs of displaced children and families and emphasizes the importance of tailored, holistic interventions to promote their well-being and resilience. Recommendations are provided for enhancing social work support and addressing systemic issues contributing to material and psychological deprivation in displacement settings.
Keywords: Social Worker; Material and psychological needs; displaces families; Dara Shakran camp